A new species of Xylechinus Chapuis (Coleoptera: Curculionidae: Scolytinae: Hylurgini) from Taiwan, with notes on its biology - Ching-Shan Lin (Taiwania, 2020)
A new species of bark beetle, Xylechinus fatsiae Lin (tribe Hylurgini) is described from Taiwan. The life cycle of the beetles in the host plant, Fatsia polycarpa (Araliaceae) is briefly described. The life cycle is completed in about one month in the laboratory.